Przygotowanie do zawodu nauczycieli w świetle raportu NIK i sporu o awans naukowy z dydaktyk przedmiotowych - Śliwerski, Bogusław (Studia Edukacyjne, 2020)
The core idea of the paper’s analysis is the incoherent school and academic government authority’s politics and the chaos caused by it in the process of educating future teachers of school subjects in general education and vocational training (general and mass one) in Poland. The author stresses the role and importance of subject teaching (detailed/specialized teaching) in relation to general teaching and models of vocational teachers’/academic education in contemporary tertiary education.